PHILOSOPHY, PANCASILA AND MODERN TECHNOLOGY - Gabrielia Febrianty Shofiana (Yuridika, 2015)
Ideology of a nation is the heart of the nation it self for any action or policies arise in the nation. The ideology is static cannot bechanged and can adapt to all conditions and ages. Pancasila as the state ideology of Indonesia should be applicable, especially in this era of modernization, so that the value contained in the ideology is not only limited to the values without meaning. Moreover, the value embodied in the ideology is capable to filter socio-cultural value of the people of Indonesia. So that Indonesian people are not losing their identity as part of the Indonesian nation has noble values that should be part of every people of Indonesia as part of a national entity in separable in every aspect of the daily life.Keywords: philosophy, pancasila, modernism.